Dynamics of the Rochelle salt NaKC4H4O6·4H2O crystal studied within the Mitsui model extended by piezoelectric interaction and transverse field - Levitskii, R.R.; Andrusyk, A.Ya.; Zachek, I.R. (Condensed Matter Physics, 2010)
We calculated dynamic dielectric permittivity of the Rochelle salt within the Mitsui model, extended by piezoelectric interaction and transverse field. Calculations were based on the parameters derived earlier within the study of thermodynamic properties of Rochelle salt. The study of dynamic properties was performed within the Bloch equation method. We showed that taking transverse field into account allows for better description of the Rochelle salt relaxation dynamics. Furthermore, we showed that taking transverse field into account results in the appearance of a resonant component in dynamic permittivity like it is observed in experiment. However, in accordance with the calculations, resonant response reveals itself within infrared frequency range, whereas in experiment it is observed within submillimeter spectral region.